2018
DOI: 10.1101/479113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A SOSEKI-based coordinate system interprets global polarity cues in Arabidopsis

Abstract: Multicellular development requires coordinated cell polarization relative to body axes, and21 translation to oriented cell division. In plants, it is unknown how cell polarities are connected 22 to organismal axes and translated to division. Here, we identify Arabidopsis SOSEKI (SOK) 23 proteins that integrate apical-basal and radial organismal axes to localize to polar cell edges. 24 Localization does not depend on tissue context, requires cell wall integrity and is defined by 25 a transferrable, protein-spec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Equivalent to Dishevelled DIX Previously, we found that the N-terminal part of the DUF966 domain of AtSOK1 is capable of homo-dimerization, and that it may resemble the DIX domains of Dishevelled and Axin, based on secondary structure predictions (Yoshida et al, 2019). The Dishevelled DIX domain undergoes dynamic head-to-tail polymerization, which results in filamentous assemblies that can be observed by electron microscopy and in protein crystals (Madrzak et al, 2015;Schwarz-Romond et al, 2007a).…”
Section: Soseki DIX Is Biochemically and Structurallymentioning
confidence: 97%
See 4 more Smart Citations
“…Equivalent to Dishevelled DIX Previously, we found that the N-terminal part of the DUF966 domain of AtSOK1 is capable of homo-dimerization, and that it may resemble the DIX domains of Dishevelled and Axin, based on secondary structure predictions (Yoshida et al, 2019). The Dishevelled DIX domain undergoes dynamic head-to-tail polymerization, which results in filamentous assemblies that can be observed by electron microscopy and in protein crystals (Madrzak et al, 2015;Schwarz-Romond et al, 2007a).…”
Section: Soseki DIX Is Biochemically and Structurallymentioning
confidence: 97%
“…The genome of the flowering plant Arabidopsis thaliana encodes five SOSEKI proteins, each of which shows polar localization during development (Yoshida et al, 2019). To identity other SOSEKI proteins in the plant kingdom, we searched the OneKP dataset (Matasci et al, 2014;Wickett et al, 2014) using a bioinformatic pipeline as previously described (Mutte et al, 2018).…”
Section: Soseki Proteins Are Shared Across Land Plantsmentioning
confidence: 99%
See 3 more Smart Citations